Hidden Life of Plants in the Science Fiction Literature in the Turn of XIXth and XXth Century - Piechota, Dariusz (The Motifs of Fauna and Flora in Literature and Culture, 2018)
This article presents an analysis and interpretation of different images of plants in the fantastic literature in the turn of 19th and 20th century. The author indicates two images of them. First (described by Wiśniowski in Flying Tree) presents plant as a very empathic creature which helps people to survive in a harsh condition. Second (described by Wells and Lovecraft) presents plant as a predacious creature which wants to kill and devour humans. Plants in science fiction literature are hybrids; they contain features typical for people. The reality in Wiśniowski, Wells and Lovecraft’s short stories was presented from biocentric perspective to sensitize the reader to the world of plants, mysterious and forgotten creatures, seemingly devoid of subjectivity. This type of literature is not only a valuable source about man-nature relationship, but primarily it questions the popular definition of nature as the primary Other, which is subordinated to human.